INTERFAITH INDIVIDUALS PERCEPTION OF THE BOYCOTT ISSUE ON PRODUCTS ASSOCIATED WITH ISRAEL - Cahyarani, Ni Made Gita; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the perceptions of interfaith individuals regarding the issue of boycotting products associated with Israel in Denpasar City. The issue of boycotting pro-Israel products is echoed by the global non-violent protest movement BDS, which calls on the global community to boycott the consumption of products from multinational companies linked to Israel. This boycott issue arose due to the military aggression carried out in 2023 when Israel attacked the Gaza Strip, destroying mosques, churches, residential homes, and hospitals that served as medical facilities for victims of Israeli military aggression. Thousands of casualties were recorded, with 70% being women and children. Consequently, the boycott issue has spread among global communities, including Indonesia.The research method used in this study is a qualitative approach with a descriptive type. The analytical framework employed as a tool in this research is Stuart Hall's reception theory. The results reveal that interfaith individuals in Denpasar have varying perceptions in responding to the boycott issue. Interviews conducted with 13 informants will be mapped according to the audience positions outlined by Stuart Hall in his Reception Theory. The distribution of informants’ positions is as follows: 2 informants are in the dominant hegemonic position, 3 informants in the negotiated position, and 8 informants in the oppositional position. In this context, the considerations affecting the perceptions of interfaith individuals are the potential impacts on economic, social, cultural, and religious aspects.